1970
DOI: 10.5642/aliso.19700702.09
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Seed Germination and Morphology among Populations of Salvia Columbariae Benth. In Southern California

Abstract: INTRODUCTIONThe finding that heat pre-treatment of the seeds of certain species of desert annuals quantitatively promotes their germination (Capon and Van Asdall, 1967) has led to a consideration of the relative effect of this factor on seeds from areas other than the desert. It was thought to be of particular interest to determine the comparative effects of heat pre-treatment on the germination of seeds of the same species from diverse habitats. Salvia columbariae Benth. is a plant ideally suited to such a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…This has been noted in particular habitats of many of the 19 local populations of Salvia columbariae from the southern Californian deserts to the coastal valleys of California (Capon and Brecht 1970). This has been noted in particular habitats of many of the 19 local populations of Salvia columbariae from the southern Californian deserts to the coastal valleys of California (Capon and Brecht 1970).…”
Section: Seed Predation and Seed Dispersal By Ants Birds And Mammalsmentioning
confidence: 88%
See 1 more Smart Citation
“…This has been noted in particular habitats of many of the 19 local populations of Salvia columbariae from the southern Californian deserts to the coastal valleys of California (Capon and Brecht 1970). This has been noted in particular habitats of many of the 19 local populations of Salvia columbariae from the southern Californian deserts to the coastal valleys of California (Capon and Brecht 1970).…”
Section: Seed Predation and Seed Dispersal By Ants Birds And Mammalsmentioning
confidence: 88%
“…Each of 19 local populations observed in a study by Capon and Brecht (1970), and 10 populations observed in a later study (Capon et al 1978), are characterized as ecotypes with individual adaptations to their specific micro-climates along the approximately 30-mile transect. Each of 19 local populations observed in a study by Capon and Brecht (1970), and 10 populations observed in a later study (Capon et al 1978), are characterized as ecotypes with individual adaptations to their specific micro-climates along the approximately 30-mile transect.…”
Section: Species Eco-genotypes and Ecotypesmentioning
confidence: 99%
“…Data from this and a previous study (Capon and Brecht, 1970) suggest that such a distribution is not attributable to the adaptability of the species as a whole but to the species being composed of several 372 ALISO ecotypes, each characterized by having individual adaptability to a specific microclimate, particularly to prevailing seasonal temperatures as they correspond with various stages in the plant's life cycle. Geographic isolation of 26 populations in southern California studied to date, their relatively small sizes, and the uniformity of seed morphology within each lend support to the belief that they are genetically homogeneous units, maintained by inbreeding through self-pollination or localized cross-pollination (Visco and Capon, 1970).…”
Section: Discussionmentioning
confidence: 51%
“…in southern California, Capon and Brecht ( 1970) showed the occurrence of a wide range of germination responses to high temperature pretreatment of the seed. The results of that study indicated the existence of possible ecotypes within the species that represent specific physiological adaptations to microenvironments at the collection sites.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely distributed in southern California from the desert to coastal zones and high elevations up to an altitude of 2100 m (Capon & Brecht, 1970). Golden chia seed matures in late spring.…”
Section: Introductionmentioning
confidence: 99%